PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DENGAN AGENCY COST SEBAGAI VARIABLE INTERVENING PADA PERUSAHAAN LQ45 TAHUN 2012-2016 - Lilik Rohmaniyah; Maslichah Maslichah; Afifudin Afifudin (Universitas Islam Malang, 2018)
ABSTRACTThis research aims to eximine the impact of capital structure, company size toagency cost; influence of capital structure, company size to company performancewith agency cost as an intervening variable. The type of this research used isexplanatory research. While sampling in this study uses purposive samplingmethod. The companies that are the object of research are LQ45 company listedon the Indonesia Stock Exchange on 2012-2016. From 45 companies studied,there were 31 companies that met the sample criteria in the study. Statisticalmethod used path analysis that is path analysis which is assisted by usingSmartPls 3. The test results show that there is a significant positive effect on thecapital structure of the agency cost and the influence is not significant betweenthe company size and agency cost, and an effect of agency cost on the company'sperformance is not significant. And there is no influence between capital structureand company size on company performance with agency cost as interveningvariables.Key words : Capital Sturcture, agency cost, firm performance, agency costand path analysis.